Strategies to Boost TikTokShop Purchases via Brand Ambassadors and Advertising - Firdaus; Martini; Sulistiyaningsih, Sri; Ismanto, Fiderius; Effendi, Meizar (Universitas Semarang, 2025)
This study explores strategies to improve product purchase decisions on TikTok Shop through the use of brand ambassadors and advertising. With the rise of social commerce, TikTok Shop has become a vital platform for digital marketing, highlighting the need for effective promotion. The research examines how brand ambassadors and advertising influence consumer behavior. A quantitative method was used, involving a purposive sample of 100 TikTok Shop users. Data were analyzed using SmartPLS 4.0, a PLS-SEM tool suitable for evaluating complex models and small samples. The measurement model assessed reliability and validity, while the structural model tested hypotheses. Results show that brand ambassadors significantly enhance consumer trust and perceived value, while advertising increases engagement and conversions. Both factors directly impact purchase intention and decisions, with intention acting as a mediator. The study concludes that combining brand ambassadors with targeted ads boosts product visibility and consumer confidence. These findings offer practical insights for businesses optimizing their TikTok Shop strategies